Une webcam à la grotte : Le sanctuaire marial de Lourdes et l’introduction des tnic - Paul BERNADOU; Sylvaine GUINLE-LORINET (Tic & Société)
DICT and the Catholic religion: the example of Lourdes shrine. – Is there a social space shared both by physical pilgrims and users of the DICT network, put to their disposal by the Marian shrine? The analysis is informed by the history of communications and an anthropological approach to reception of the communicational process of pilgrimage and new communications technologies in this Catholic shrine. We propose an anthropological perspective to identify the similarities and differences between the behaviour of "physical" pilgrims to the shrine and Internet users. By inference, this could provide indications as to the spaces shared by these respective communities.